2022
DOI: 10.1177/20503121221095942
|View full text |Cite
|
Sign up to set email alerts
|

‘I got to understand what it means to be a cancer patient’: Qualitative evidence from health professional cancer patients and survivors

Abstract: Objective: The study sought to (1) examine healthcare professionals’ (HCPs) lived experiences of cancer and (2) generate evidence to inform policy and clinical practice for cancer care. Methods: This was a qualitative study conducted between January and December 2020 on HCPs who were ill with, or who had survived cancer in Uganda. Purposive sampling was used. A demographic form and an open-ended topic guide were used to collect data. Face-to-face and telephone interviews were conducted in English; audio-record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…All narrated how getting a cancer diagnosis adversely impacted their psychological and social well‐being, and ‘metastasized’ to their loved ones (family, friends, work colleagues) who also suffered psychological distress, shock, worry, etc. Stigma related to cancer and non‐cancer illnesses has been reported in other medical literature and studies conducted with health professional patient populations, and is a risk factor to, and exacerbates psychological morbidity (Fox et al, 2009; Kay et al, 2004, 2008; Marsh, 2022; Natuhwera et al, 2022). There is thus, an urgent need to identify strategies to destigmatize cancer, as stigma could negatively impact healthcare‐seeking behaviours, and lead to poor cancer treatment outcome.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…All narrated how getting a cancer diagnosis adversely impacted their psychological and social well‐being, and ‘metastasized’ to their loved ones (family, friends, work colleagues) who also suffered psychological distress, shock, worry, etc. Stigma related to cancer and non‐cancer illnesses has been reported in other medical literature and studies conducted with health professional patient populations, and is a risk factor to, and exacerbates psychological morbidity (Fox et al, 2009; Kay et al, 2004, 2008; Marsh, 2022; Natuhwera et al, 2022). There is thus, an urgent need to identify strategies to destigmatize cancer, as stigma could negatively impact healthcare‐seeking behaviours, and lead to poor cancer treatment outcome.…”
Section: Discussionmentioning
confidence: 89%
“…On top of the emotional disturbances following diagnosis, inadequate, and/or contradictory information about the illness from HCPs exacerbated the emotional distress of some participants. Disabling psychological symptoms have been reported in studies with non‐professional cancer patients (Natuhwera et al, 2022 ; Van Beek et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…Our finding related to cultural values, therefore, has educational and health policy implications for sub-Saharan African countries. Currently, the training of general medical practitioners in Uganda still largely emphasizes the medical model and not holistic and culturally sensitive care (bio-psycho-social care) which are relevant to the modern oncological approach to the management of patients with cancer [ 39 , 40 ]. This may partly explain why patients with cancer prefer to use the services of TMPs or even abandon medical care for traditional medicine leading to late referrals to hospitals and poor prognosis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients also had uncontrolled symptoms, including pain, worry, and despair, which prolonged physical and mental suffering and put a strain on careers. [17][18][19][20] A study conducted in Uganda and Zimbabwe showed that community members and families stigmatize patients with cancer disease, often stemming from misunderstanding, misconception, and fear. Such stigma can lead to social isolation for people with cancer.…”
Section: Poormentioning
confidence: 99%
“…The diagnosis is often seen as an irreversible event that worsens the discomfort and pain symptoms in patients' illness trajectory. [18,21] Another study reported that people with incurable diseases often worry about what will happen to them in the future, as it is difficult to predict how the disease will affect them. This can lead to stress and anxiety, as they may feel uncertain about their prognosis.…”
Section: Poormentioning
confidence: 99%